(untitled) (Conferencea, 2023)
The rights of thousands of Uzbeks were violated as a result of the "Cotton Case" and "Uzbeks Case" repressive policies that lasted from September 1983 to May 1989. The article talks about the processes of ending illegal investigative processes carried out in Uzbekistan.